The risk of early-onset neonatal sepsis in preterm infants with maternal histologic chorioamnionitis - IGK Winata Adnyana; Soetjiningsih Soetjiningsih (Indonesian Pediatric Society Publishing House, 2016)
Background Chorioamnionitis, usually a subclinical condition, may cause preterm delivery and long-term morbidity. Objective The objective of this study was to determine the risk of early-onset neonatal sepsis in preterm infants with maternal histo- logic chorioamnionitis (HCA). Methods This was a prospective cohort study of preterm infants born at Sanglah Hospital, Denpasar from September 2002 to Feb- ruary 2004. Histopathological examinations of the subjects' placen- tas were done and the infants were monitored for 72 hours for clini- cal signs of early-onset neonatal sepsis. Maternal and neonatal risk factors were analyzed using multivariate statistical analysis. Results Eighty-two preterm infants were included, of which 41 were positive for maternal HCA. Twenty-five (61%) of the infants posi- tive for maternal HCA developed early-onset neonatal sepsis, com- pared to 5 (12%) of those negative for maternal HCA (RR=5, 95%CI 2.12;11.78). Nine infants died from early onset neonatal sepsis. Eight of them had positive HCA, and only one had negative HCA. The average length of hospital stay between infants with and with- out maternal HCA did not differ significantly [12.0 (SD 5.08) vs. 12.6 (SD 1.34); P=0.80]. Logistic regression model analysis iden- tified only HCA as a significant risk factor for early-onset neonatal sepsis (OR=6.9, 95%CI 2.0;23). Gestational age (OR=1.3, 95%CI 0.8;2.0), birth weight (OR=1.0, 95%CI 0.9;1.0), and neonatal as- phyxia (OR=1.0, 95%CI 0.1;4.4) were not found to be significant risk factors. Conclusion Preterm infants with maternal histologic chorioamnionitis are at a higher risk for developing early-onset neonatal sepsis